Respostas
respondido por:
19
Vamos achar as raizes
Sendo a = 1 b = -5 c = 0
Primeiro vamos achar delta
Delta = b² - 4.a.c
Delta = -5² -0
Delta = 25
Agora usar baskara:
X = -b+-√Delta/2.a
X = 5+-√25/2
X = 5+- 5/2
X'= 5+5/2 = 5
X'' = 5-5/2 = 0
Resposta A
Sendo a = 1 b = -5 c = 0
Primeiro vamos achar delta
Delta = b² - 4.a.c
Delta = -5² -0
Delta = 25
Agora usar baskara:
X = -b+-√Delta/2.a
X = 5+-√25/2
X = 5+- 5/2
X'= 5+5/2 = 5
X'' = 5-5/2 = 0
Resposta A
respondido por:
8
Usa Bhaskara.
-(-5)⁺⁻√(-5)²-4.1.0 tudo dividido pra 2.1
Δ=(-5)-4.1.0
Δ=25-0
Δ=25
5⁺⁻√25 tudo dividido por 2
x₁=(5+5):2
x₁=10:2
x₁=5
x₂=(5-5):2
x₂=0:2
x²=0
x={5,0}
-(-5)⁺⁻√(-5)²-4.1.0 tudo dividido pra 2.1
Δ=(-5)-4.1.0
Δ=25-0
Δ=25
5⁺⁻√25 tudo dividido por 2
x₁=(5+5):2
x₁=10:2
x₁=5
x₂=(5-5):2
x₂=0:2
x²=0
x={5,0}
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás